Effect of varying the force direction on maxillary orthopedic protraction - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2002)
The aim of this study was to examine the effect of varying the force direction on maxillary protraction. A total of 20 patients with class III maxillary retrognathism were randomly divided into two groups. Group 1 was comprised of nine patients with a mean age of 8.58 years, and group 2 was composed of 11 patients with a mean age of 8.51 years. Both groups received a cap splint-type rapid palatal expander and the screw was activated twice a day for 10 days. After the expansion procedure the face mask protraction procedure was initiated. In group 1, we applied the force intraorally from the canine region with a forward and downward direction at a 30degrees angle to the occlusal plane. In group 2, the force was applied extraorally 20 mm above the maxillary occlusal plane. In both groups a unilateral 500 g force was applied and the patients were instructed to wear the face mask for 16 h/d for the first three months and 12 h/d for the next three months. The Wilcoxon sign rank test was used to evaluate the effect of the two different face masks, and a Mann-Whitney U-test was carried out to evaluate the differences between the two groups. The results showed that both force systems were equally effective to protract the maxilla; however, in group 1 we observed that the maxilla advanced forward with a counter-clockwise rotation. In group 2 we observed an anterior translation of maxilla without rotation. The dental effects of both methods were also different. The maxillary occlusal plane did not rotate in group 1, in contrast to the clockwise rotation in group 2. The maxillary incisors were proclined slightly in group 1, but in contrast they were retroclined and extruded in group 2. In conclusion, the force application from near the center of resistance of the maxilla was an effective method to prevent the unwanted side effects, such as counter-clockwise rotation of the maxilla, in group 1. The group 2 results suggest. that this method can be used effectively on patients who present as class III combined with an anterior open bite.
Keywords: class III; maxillary retrognathia; face mask; protraction headgear; biomechanics; PALATAL EXPANSION; PROFILE CHANGES; FACE-MASK; SKELETAL; HEADGEAR